P283 A rare case of vertebral osteomyelitis caused by co-infection of Candida and Mycobacterium Tuberculosis: a double trouble. (20th September 2022) - Sharma, Shivang; Samantaray, Subhashree; Ravindra, Akshatha; Naguthevar, Santhanam; Khatod, Yash; R, Neetha T; Kumar, Deepak; Meena, Durga Shankar; Bohra, Gopal Krishna; Garg, M K; Tiwari, Sarbesh; Kombade, Sarika
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM:   Introduction: The vertebral osteomyelitis can be pyogenic (bacterial), non-pyogenic-granulomatous (tuberculosis, brucella, fungi), or parasitic. Fungal spondylodiscitis only accounts for 0.7%-2.7% of all spinal infections. Tubercular vertebral osteomyelitis has a high prevalence in developing countries like India. Co-infection of the spine by both fungal and tuberculous organisms is rare, there is only one case that has been reported till now in our literature review. Case: A 62-year-old man presented with complaints of lower back pain for 3 months and fever with chills for 1 month. He had done multiple OPD visits at other centers for his lower back pain in the past 2 months, where a whole spine MRI was done which was suggestive of prolapsed intervertebral disc at multiple spinal segments- maximum at L4-L5 causing indentation of nerve roots for which he was given 3 days of IV and followed by 15 days of oral methylprednisolone. On steroids, patient developed fever and increased lower back pain for which he was admitted. Repeat MRI spine revealed features s/o axial spondylo-arthropathy. At this point, he was referred to our center for further management and was admitted. He was a known case of diabetes and underwent bilateral DJ stenting for nephrolithiasis 3 months before. On post-operative day 4, he had developed low back ache. He was vitally stable but febrile, unable to sit or walk without support. He also had tingling and numbness in bilateral lower limbs. Laboratory results showed raised inflammatory markers. Vertebral biopsy was done, CBNAAT was negative, while culture revealed growth of Candida albicans . He was started on injection of fluconazole 800 mg loading dose followed by 400 mg daily. After 5 days he got afebrile but, lower limb weakness and lower back pain persisted. Hence a repeat vertebral biopsy was planned. Surprisingly, CBNAAT of the biopsy sample detected very low MTB and indeterminate rifampicin resistance, following which the patient was initiated on weight-based HRZE regimen along with fluconazole. Currently, patient is afebrile and his lower limb weakness has improved with lower limb muscles power 0/5 to 3/5 on follow-up after a month. Conclusion: Non-pyogenic vertebral osteomyelitis due to tuberculosis is common in a high TB burden country like India. Even though Candida is a rare causative agent, but should always be considered as a differential in patients having risk factors. In our patient abdominal surgery, DM and steroids could have predisposed for developing Candida vertebral osteomyelitis. The possibility of co-infection of TB and Candida should not be ignored in patients who have risk factors, especially if they present with clinical and radiological signs befitting its manifestations. High suspicion and tissue diagnosis remain crucial factors for early diagnosis and aids in better clinical outcomes.